ANALISIS SHIFT SHARE PADA TRANSFORMASI SEKTOR PERTANIAN DALAM PEREKONOMIAN WILAYAH DI BENGKULU - Esti Pasaribu; Merri Anitasari; Romi Gunawan; Retno Agustina Ekaputr; Novi Tri Putri (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to identify the changes of the agricultural sector in Bengkulu using the shift-share analysis model. While Bengkulu is always the poorest area in Sumatera Island so it is important to look further into the economic structure of Bengkulu and to compare the sectoral distributions with Sumatera’s. The type of this research is a descriptive analysis using secondary data in the 2010-2016 period. Shift share analysis using Esteban Marquilas’s results describes that the agricultural sector is no longer the backbone of Bengkulu economy. The analysis shows that the value of competitive advantage in Bengkulu Province was negative, while specialization value (Aij) was negative too. In aggregate, Bengkulu Province has no competitive advantage and also specialization. This means Bengkulu Province needs a breakthrough to get out of poverty, especially by looking at the economic structure.